Predictors of Videoconference Fatigue: Results From Undergraduate Nursing Students in the Philippines - Ryan Michael F. Oducado; Maria Teresa R. Fajardo; Geneveve M. Parreño-Lachica; Jestoni D. Maniago; Paulo Martin B. Villanueva; Ma. Asuncion Christine V. Dequilla; Hilda C. Montaño; Emily E. Robite (Asian Journal for Public Opinion Research)
Driven by the need for remote learning, the COVID-19 pandemic led to the rise of use of videoconferencing tools. Scholars began noticing an emerging phenomenon of feeling tired and exhausted during virtual meetings. This study determined the predictors of videoconference or Zoom fatigue among nursing students in a large, private, non-sectarian university in the Philippines. This cross-sectional online survey involves 597 nursing students in the Philippines using the Zoom Exhaustion and Fatigue Scale. Multiple linear regression analysis was used to examine predictors of videoconference fatigue. Results indicated that nursing students experienced high levels of videoconference fatigue. Gender, self-reported academic performance, Internet connection stability, attitude toward videoconferencing, frequency, and duration of videoconferences predicted videoconference fatigue. The regression model explained 25.3% of the variances of the videoconference fatigue. Videoconference fatigue is relatively prevalent and may be taking its toll on nursing students. Developing strategic interventions that can protect or mitigate the impact of fatigue during virtual meetings is needed.